Pengetahuan dan Sikap Suami tentang Pijat Oksitosin pada Ibu Menyusui - Muzayyaroh Muzayyaroh; Suyati Suyati (Oksitosin : Jurnal Ilmiah Kebidanan, 2023)
Oxytocin massage is an action performed using massage on the 5-6 ribs and up to the scapula. The massage aims to stimulate the smooth flow of breast milk, increase milk filling to the breast, provide a sense of comfort for the mother. Success of a mother in breastfeeding her baby is very dependent on the support of various parties, especially the husband. Active role of the husband by giving oxytocin massage is one form of support that can be done for breastfeeding mothers so that they can facilitate breastfeeding. Study aims to find out how the level of knowledge and attitudes of husbands carrying oxytocin massage in nursing mothers. Research was a type of descriptive research. Sample in this study were husbands of breastfeeding mothers is 30 respondents. Sampling with a purposive sample. Results showed that most of the husbands' knowledge about oxytocin massage had sufficient knowledge, namely 53%, and the husband's attitude regarding oxytocin massage, the majority had an adequate attitude, namely 54%. Conclusion of this study was that most husbands had fairly good knowledge and attitudes. Suggestions for health workers is to increase counseling or training activities for both breastfeeding mothers and their husbands about oxytocin massage.